Moral Reasoning and Moral Behavior: Intersections of Reasoning with Aggressive Forms and Functions in Early Childhood. Issue 4 (19th May 2021) - Baker, Erin Ruth; Liu, Qingyang
ABSTRACT: Research Findings: Children's capacities for complex socio-moral reasoning carries across domains; similarly, children's aggressive behaviors changes as a function of context. However, with a few exceptions, little research has considered children's socio-moral reasoning and aggressive subtypes in concert. The goals of the current study were to consider these phenomena together, and to explore possible gender differences. In the current study, teachers reported children's (N = 130, Mage = 56.05) aggressive behaviors (physical proactive, physical reactive, relational proactive, and relational reactive), and children completed an open-ended story interview pertaining to unintentional, multifaceted harm in order to assess their socio-moral reasoning strategies (moral domain: psychological harm, property damage, resource distribution; conventional domain: rule adherence). Practice or Policy: Findings support the form-by-function approach to aggression, and support the notion that children's reasoning is an important factor in understanding aggressive subtypes. For example, care-oriented, but not justice-oriented, strategies in the moral domain corresponded with lower rates of aggression, but not all types of aggression and not for all ages. Moreover, several age by gender interactions occurred, suggesting that aggressive behaviors are not uniform across early childhood. Educators and parents may find utility in approaching children's misbehavior with appropriative responses that are sensitive to children's moral reasoning.